Complexos semi-sanduíche de RuII/areno e produtos naturais: uma promissora combinação para novos metalofármacos - Araujo Neto, João Honorato de (2020)
This thesis presents the synthesis, characterization and evaluation of antitumor activity of nineteen neutral and monocatonic organometallic complexes containing ligands derived from natural products. The complexes were divided into three Series based on the employed classes of natural products (all coordinated by oxygen atoms in the bidentate form), which are: Series A, complexes of general formula [RuLx(η6-p-cimene)(PPh3)], where PPh3=triphenylphosphine and Lx=benzoic acid (A1), p-hydroxybenzoic acid (A2), p-nitrobenzoic acid (A3) and terephthalic acid (A4); Series B, complexes of general formula [RuClLx(η6-p-cimeno)] (B1-B3), [RuCl2(η6-p-cimeno)(PPh3)] (B4-B6), fac- [RuClLx(S-DMSO)3] (B7-B9) and cis-[RuClLx(S-DMSO)2(PPh3)] (B10-B12), where PPh3=triphenylphosphine and Lx=lawsone, lapachol and 3-styryl-lawsone; Series C, complexes of general formula [RuLxCl(η6-p-cimeno)] (C1), [RuLx(η6-p-cimeno)(PPh3)]PF6 (C2) and [Ru(η6-p-cimene)(PEt3)]PF6 (C3), where PPh3=triphenylphosphine, PEt3=triethylphosphine and Lx=alizarin. All complexes were characterized by elemental analysis, molar conductivity, infrared absorption spectroscopy, 1D and 2D nuclear magnetic resonance (31P {1H}, 1H and 13C {1H}), mass spectrometry and single-crystal X-ray diffraction. The stability of the compounds was investigated in solvents for biological tests, where Series A and C showed stability in the mixture used. In other hand, in Series B, B1-B6 were unstable in these mixtures, resulting in the complexes of the general formula fac-[RuClLx(S-DMSO)3] (B7-B9) and cis-[RuClLx(S-DMSO)2(PPh3)] (B10-B12). The cytotoxicity of the complexes were evaluated in the tumor cells of breast (MDA-MB-237 and MCF-7), lung (A549), prostate (DU-145) and the corresponding non-tumoral cells of breast (MCF-10A), lung (MRC-5) and prostate (PNT2) cell lines, varying the number of strains in each Series. In Serie A, the A1-A2 (IC50=11,0-19,3 μM) were more active than A3 (IC50=40,5-60,7 μM) in all tumor cell lines tested, with the highest selectivity index displayed by A1 for MDA-MB-231 cell line (3,5). In Series B, the influence of triphenylphosphine (PPh3) on the IC50 values were observed. The complexes with PPh3 were more active than those ones containing the chloride ligand, besides that the p-cymene labilization became the complexes without PPh3 (B1-B3, IC50>10 μM) more active, this comparing with B7-B9 (IC50= 8,01-0,70 μM). Additionaly, in the complexes B4-B6 (IC50=18,09-0,33 μM) when compared with B10-B12 (IC50=17.36-0,31 μM) it is noted that the labilization of the arene perform insignificant effect on the citoxicity of the complexes. In Series C, C2 (IC50=17.8-6.5 μM) was the most cytotoxic complex, while C1 (IC50=32,8-> 100 μM) and C3 (IC50=41.6-> 100 μM) were less active and selective. The stable complexes of B and C Series were evaluated for DNA interaction, showing only weak interactions, except for C1, which exhibited strong/moderate interactions of covalent type. In general, the complexes were able to inhibit the colony formation, A1, C2 and C3 inhibited cell migration and B6, B12 were able to induce morphological changes in tumor lines. In addition, A1, B3, B6, B9, B12 and C2 promoted the cell cycle arrest in the Sub-G1 phase. In A Series it was found that the A1 is able to accumulate in MDA-MB-231 cells (ICP-MS data) and in the C Series, the fluorescence displayed by C1 allowed to observe the cellular uptake in MDA-MB-231 cells, through the confocal microscopy technique, showing the internalization of the complex.